Effect of Succinate Crystalloid Solution on Hemostasis in Children with Severe Community-acquired Pneumonia - Vladimir V. Lazarev; Pavel E. Anchutin; Manuel M. Megeryan; Mikhail V. Bykov; Dmitry A. Smirnov; Tatiana A. Pchelicnceva; Nikolay S. Frolov; Khurzada M. Makhachilaeva; Boris I. Golubev; Elena A. Spiridonova (Общая реаниматология, 2024)
Aim of the study. To improve outcomes in children with severe community-acquired pneumonia (CAP) by including succinate-containing crystalloid solution (SCCS) in the treatment plan.Materials and methods. The study included 100 patients diagnosed with CAP. SCCS was administered to 24 patients from the prospective (main) group, divided into 2 equal subgroups of 12 subjects who received SCCS with the infusion rate of 2.5 ml/kg/h (subgroup 1) and 5.0 ml/kg/h (subgroup 2). Treatment of 76 patients in the retrospective (control) group did not include SCCS.Results. Greater decreases in D-dimer (by 418.5 ng/mL vs. 137.0 ng/mL, P=0.026) by day 3 and in fibrinogen (by 1.7 g/L vs. 0.2 g/L, P0.001) by day 3 and (3.8 g/L vs. 0.5 g/L, P=0.002) by day 5 of hospitalization were found in children from the main group vs. the control group. Fibrinogen levels decreased in both study subgroups, although subgroup 1 had significantly higher fibrinogen levels on day 2 of ICU stay (P=0.034). A significant increase in activated partial thromboplastin time (aPTT) of 9.7 seconds was observed on day 3 in the main group versus 2.9 seconds in the control group (P0.001). There was a direct correlation between fibrinogen level and neutrophil count on day 2 of ICU stay (R=0.479, P=0.033). Conclusion. The use of SCCS in the treatment of severe CAP helps to prevent thrombotic complications, reduces hypoxia-induced changes in the coagulation system, and enhances the effects of unfractionated heparin. SCCS infusion at a rate of 5.0 mL/kg/h effectively reduces the levels of hypercoagulation markers, while its administration at a rate of 2.5 ml/kg/h potentiates the effects of unfractionated heparin. The effects of SCCS on hemostasis in severe CAP are equivalent to those of a moderate anticoagulant.